Early Mobilization Intervention: Non-Drug Solutions for Post-Fracture Surgery Pain in the Lakey Room of West Provincial General Hospital - Dewi Nur Sukma Purqoti; supriyadi supriyadi; Ernawati; Mita Yulia Rahman (Institut Kesehatan YARSI Mataram, 2025)
Based on data from the Central Surgical Installation (IBS) at the NTB Provincial Hospital, cases of orthopedic injuries have been increasing every year and ranked fourth in surgical cases. The purpose of early mobilization is to facilitate blood circulation, reduce pain, and enhance wound healing. The aim of this research is to determine the effect of early mobilization on pain intensity reduction in post-operative fracture patients in the RSUD NTB. The research method used is a Pre-Experimental design with a One Group Pretest Post test Design. A sample of 12 post-operative fracture patients meeting the inclusion criteria was used, and the sampling technique employed was Total Sampling. The inclusion criteria for this study were patients aged 25-50 years, undergoing surgery for the first time and cooperative in the research process, the instrument used to measure the level of pain using the visual analog scale (VAS). This research was tested using the Wilcoxon test, showing that out of 12 samples pain decreased with a significance value of 0.002 or significance ≤0.05, meaning there is an effect of early mobilization on the reduction of pain intensity in post-operative fracture patients. It is expected that in the future, healthcare institutions will further optimize the implementation of early mobilization for post-operative fracture patients. ABSTRAK Berdasarkan data Instalasi Bedah Sentral (IBS) di RSUD Provinsi NTB Kasus cedera Orthopedi setiap tahun mengalami peningkatan dan menjadi urutan ke empat kasus bedah. Pelaksanaan mobilisasi dini bertujuan untuk memperlancar sirkulasi darah, menurunkan rasa nyeri, dan meningkatkan penyembuhan luka. Tujuan penelitian adalah untuk mengetahui pengaruh mobilisasi dini terhadap penurunan intensitas nyeri pada pasien post operasi fraktur di ruang lakey RSUD Provinsi NTB. Metode penelitian yang digunakan adalah Pra-Eksperimental dengan desain One Grup Pretest Post test Design. Sampel sejumlah 12 pasien post-op Fraktur yang sesuai dengan kriteria inklusi dan teknik sampling yang digunakan adalah Total Sampling. Kriteria inklusi untuk studi ini adalah pasien berusia 25-50 tahun, menjalani operasi untuk pertama kalinya dan kooperatif dalam proses penelitian, instrumen yang digunakan untuk mengukur tingkat nyeri menggunakan skala analog visual (VAS). Penelitian ini diuji menggunakan uji Wilcoxon didapatkan dari 12 sampel menunjukkan penurunan nyeri dengan nilai signifasi 0,002 atau signifikasi ≤0,05 artinya ada pengaruh mobilisasi dini terhadap penurunan intensitas nyeri pada pasien post operasi fraktur. Diharapkan kedepannya dalam instansi pelayanan kesehatan agar lebih mengoptimalkan untuk menerapkan mobilisasi dini pada pasien post operasi fraktur